مفهوم نظام حوكمة شركات المساهمة: النظرة القانونية مقارنة بالشريعة الإسلامية = Corporate Governance in Shareholding Companies: Comparing Legal Perspective and Position of Shari’ah - Hasan, Aznan; Al Timimi, Harith Amir Hasan (Kolej Islam Darul Ridzuan, Perak, 2015)
This study examines the concept of corporate governance in shareholding companies and the legal perspective in comparison with the position of Shari’ah. The purpose of governance is to instil confidence among the stakeholders that the Boards of Directors are applying a diligent legal and administrative framework, to avoid potential administrative and financial failures and corruption. The study has proceeded by defining the concept of governance from linguistics, accounting, administrative, and legal perspectives. The study also discusses the stands of international organisations on the issue of corporate governance. Then, it is proceeded by discussing the concept of corporate governance from Shari’ah point of view. The study found that even with the absence of the term “company governance” in Islamic Law, the concept of corporate governance is in line with the Shari’ah and that their scholars have clearly referred to it in their literature. The study has used the descriptive, analytical, inductive and comparative methodology in analyzing the subject matter.